ANALISA PENGARUH PROMOSI JABATAN DAN DISIPLIN KERJA TERHADAP KEPUASAN KERJA PT. MENARA ABADI PERSADA MEDAN - Zennyta Zennyta; Alfonsius Alfonsius (STIE-PMCI, 2018)
PT. Abadi Tower Persada Medan is a company engaged in the sale of Gypsum. In operation, Gypsum's sales rate in the company has decreased. This sales decline reflects the decline in employee's ability to work where due to employee's dissatisfaction problem. Job dissatisfaction of employees in the company arises because of the promotion of positions assessed by employees are less fair, do not appreciate the devotion and service as long as employees work in the company. Employee dissatisfaction leads to low employee discipline. The formulation of the problem in this research is whether there is influence of promotion and job discipline to job satisfaction PT. Menara Abadi Persada Medan.The method used in this research is survey approach, this type of research is descriptive quantitative and the nature of this research is descriptive explanatory. Population in this research is permanent employee at PT. Menara Abadi Persada Medan with a total of 57 permanent employees. In this study, the population in this company is 57 employees so that the number of samples taken is the total of the entire population in the company. Data collection techniques were conducted with interviews, questionnaires, and documentation studies. The types and sources of this research data are primary data and secondary data. The data analysis model used to answer the hypothesis is multiple regression.The results showed that partially and simultaneously promotion of office and work discipline affect the job satisfaction of PT. Menara Abadi Persada Medan. Partially, promotion positions have more dominant influence on job satisfaction of PT. Abadi Persada Tower compared to work discipline.Â Keywords: Job Promotion, Work Discipline, Job Satisfaction